El turismo slow como alternativa para el desarrollo sostenible en la comunidad del milenio A´I Cofan Dureno al 2030 - Caiza, Clara; Andrade Ruiz, Wilian Patricio (Revista Ecos de la Academia, 2023)
The present research analyzes the tourism potential of the Millenium A’I Cofán Dureno community to become a slow destination by the year 2030. Theoretical references include Lagos (2018), Di Clemente (2011), Sosa (2012), De Luis Blanco (2011); UNWTO (2021); UN (2021); Cittaslow (2020). The methodology was qualitative, framed in the voluntarist school of foresight, taking into consideration the sustainability requirements of the Cittaslow. The prospective SWOT, Regnier’s Abacus, checklist and Peter Schwartz’s Axes techniques were used. In conclusion, it was determined that the strengths of the community are linked to its natural and cultural wealth. Likewise, the strong spiritual significance of the Aguarico River for the members of the community was evident. It was also determined that the community meets most of the sustainability indicators dictated by the Slow Movement.